An Investigation on Chloride and Akaline Impurities of Pelletizing Plants in Iran - A. Abazarpoor; R. Hejazi; M. Saghaeian; V. Sheikhzadeh (International Mineral Processing Congress, 2018)
The research aimed to compare the chemical analysis (K, Na, Cl) of Iranian concentrate plants, which are the main source of materials corrosion in the pelletizing plants. Cl alongside alkaline elements (especially K) may cause corrosion and plug in the grate plates and other involved equipment. Therefore, it is tried in the processing plants to remove impurities from the concentrate to prevent potential problems in pelletizing and iron/steel making processes. Part of these impurities are existed in the nature of ores and others are sourced in the processing water. Various samples from the largest Iranian concentrate plants including Chadormalu, Gol-e-Gohar, Jalal-Abad and Sechahun were prepared to investigate the possibility of alkaline problems for each samples. The amount of Cl, K and Na of Chadormalu sample was obviously low and therefore no alkaline problem is expected. The Cl content of Gol-e-Gohar sample was high (980 ppm) while amount of K was less (0.008 Wt. %). Due to low content of K, most of Cl will release as Cl2 or HCl and so problems caused by KCl plugging would not be a problem. The amount of Cl in Sechahun case was nearly same as Jalal-Abad (400-600 ppm), higher than Chadormalu and less than Gol-e-Gohar samples. However, the K content was higher than all samples (0.04 Wt. %). Therefore, the amount of evaporated K would be 2-4 times more than other samples. Since the amount of Cl and K is simultaneously higher than usual iron ores, therefore alkaline problems may be a serious prevention factor for the continuous operation of this plant. In order to solve this problem some counter-measures is suggested and discussed including cleaning system, partial dust enriched with KCl removal and variation in the materials type of involved equipment.